Adverse Events Associated With Cryolipolysis: A Systematic Review of the Literature. (October 2020) - Hedayati, Bobak; Juhász, Margit; Chu, Sherman; Mesinkovska, Natasha Atanaskova
Abstract : BACKGROUND: Cryolipolysis is a popular procedure for people seeking noninvasive body contouring. As with any novel therapy, it is critical for providers to familiarize themselves with related adverse events (AEs), to provide appropriate information to patients before treatment. OBJECTIVE: To describe reported complications and AEs associated with cryolipolysis. MATERIALS AND METHODS: A systematic review was completed using the PubMed database and following search terms: "cryolipolysis" or "lipocryolysis" or "CoolSculpting." Only randomized clinical trials, prospective cohort studies, retrospective studies, case series, and case reports describing AEs related to cryolipolysis as well as studies written in English were included for review. RESULTS: Fifty-three articles were included in this review. The most common AEs associated with cryolipolysis were treatment site erythema, numbness/paresthesia, bruising, and edema. More serious complications of cryolipolysis include severe/persistent pain, dysesthesia, skin hyperpigmentation, motor neuropathy, and paradoxical adipose hyperplasia. CONCLUSION: Cryolipolysis is a safe option for patients seeking noninvasive body contouring. Most reported AEs are minimal and resolve quickly. It is important that physicians are aware of serious, irreversible AEs and are prepared to counsel patients appropriately before treatment. Abstract : Supplemental Digital Content is Available in the Text.